Hybrid Approach For Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
The Wireless Sensor Network is a widely used approach mainly used for real time applications. Real time applications raise various fundamental problems like limited energy resources.  We propose a paper on Hybrid approach which is the combination of Grid based approach and Cluster based approach. the main task of a sensor network is to minimize the energy consumption of wireless sensor network. So On Hybrid approach grid based network depends on the location where it is divided into different grid sizes. And in clusters, wireless sensor network, cluster head works like a base station that send all sense information to the sink node of the network. We are working on QualNet tools to simulate the scenario of the Grid based cluster network.